Between cunning states and unaccountable international institutions: Social movements and rights of local communities to common property resources - Shalini Randeria (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
The paper analyses the new architecture of global governance which is characterised by unaccountable international institutions and scattered sovereignties. It examines the dilemmas of civil society actors (social movements and NGOs) involved in protecting the rights of local communities through strategic issue-based alliances with the state or the World Bank, whose legitimacy they question in other contexts. The cunning state remains a central actor in selectively transposing neo-liberal policies to the national terrain and capitalises on its perceived weakness in order to render itself unaccountable to its citizens. The argument draws on empirical material from India around conflicts over the patenting of genetic resources, biodiversity conservation, forced displacement and privatisation of common property resources. It cautions against attributing homogeneity to the state whose logic of action may differ at the federal and regional level; it delineates the shifting contours of the boundary between the public and the private as well as the growing entanglement between civil society and state; and it unpacks civil society to show that there is little in common between advocacy networks involved in a politics of contention and powerful NGOs rendering expert advice to states and international institutions. – – Dieser Aufsatz untersucht die neue Architektur des "globalen Governance", die durch nicht-rechenschaftspflichtige internationale Institutionen und geteilte Souveränität gekennzeichnet ist. Er analysiert die Dilemmata zivilgesellschaftlicher Akteure (soziale Bewegungen, NROs), die kurzfristige strategische Bündnisse mit dem Staat oder der Weltbank eingehen, um die Rechte lokaler Gemeinschaften schützen zu können. Der ,,listige Staat“ ist zugleich Opfer wie Gestalter neoliberale Prozessen und versucht Kapital aus seiner vermeintlichen Schwäche zu schlagen, um sich der Verantwortung gegenüber den eigenen Bürgern zu entziehen. Die Thesen des Aufsatzes stützen sich auf empirisches Material aus Indien zur Patentierung genetischer Ressourcen, dem Schutz der Biodiversität, der Zwangsumsiedlung, und der Privatisierung allgemein zugänglicher natürlicher Ressourcen. Es wird gezeigt, dass der Staat nicht als homogener Akteur gesehen werden darf, da sich die Logik staatlichen Handelns auf der föderalen und der regionalen Ebenen unterscheidet. Indem die Politik der basisnahen Netzwerke, die gegen den Staat mobilisieren, von den einflussreichen NROs, die den Staat und internationale Institutionen als Experte beraten, differenziert wird, lässt sich einerseits die sich verändernde Grenzziehung zwischen Öffentlichem und Privatem thematisieren, andererseits können die zunehmenden Verflechtungen zwischen Zivilgesellschaft und Staat erörtert werden.
Keywords: 300